Arduino-based solution for in-carAbandoned infants' controlling remotely managed by smartphone application - Visconti, Paolo (Array, 2019)
This manuscript deals with V2V/V2I (Vehicle-toVehicle and Vehicle-to-Infrastructure) communication systems developed for smart city applications, with the aim to provide new services and tools for making driving safer and improving the human lifestyle. The considered systems can be supported by suitable software applications for making the services more accessible. In this context, research groups and automotive companies are currently developing systems against children abandonment in unattended vehicles and are installing them on new car models. In this paper, an innovative Arduino-based control system against children abandonment in cars is described. It introduces new functionalities respect to systems reported in literature or already on the market, in order to improve safety and reliability. The proposed system integrates a mobile app, which gives the possibilities of receiving alert or status messages, along with images directly acquired from car cockpit. In addition, the app allows to remotely control several car functionalities, such as horn activation, windows lowering and doors locking/unlocking. The wide set of employed sensors allows to solve some shortcomings of detectability presented by similar detection systems, thanks to a proper cross-checking of the acquired information.